2017
DOI: 10.1021/jacs.7b09268
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Dynamical Couplings in Mutated scFv Antibody Fragments into Stabilizing and Destabilizing Effects

Abstract: Conformational fluctuations within scFv antibodies are characterized by a novel perturbation-response decomposition of molecular dynamics trajectories. Both perturbation and response profiles are stratified into stabilizing and destabilizing conditions. The linker between the VH and VL domains exhibits the dominant dynamical response by being coupled to nearly the entire protein, responding to both stabilizing and destabilizing perturbations. Perturbations within complementarity-determining regions (CDR) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…8C). In a similar case, a recent MD simulation of single-chain Fv antibodies found that the linker between the V H and V L domains exhibited the dominant dynamical response by being coupled to nearly the entire protein (38). Our MD simulations are consistent with previous H/D exchange experiments showing that pMHC binding induced a global reduction in TCR A6 flexibility that included the C␤ FG loop (28).…”
Section: Allosteric Changes In T Cell Receptor Induced By Peptide-mhcsupporting
confidence: 87%
“…8C). In a similar case, a recent MD simulation of single-chain Fv antibodies found that the linker between the V H and V L domains exhibited the dominant dynamical response by being coupled to nearly the entire protein (38). Our MD simulations are consistent with previous H/D exchange experiments showing that pMHC binding induced a global reduction in TCR A6 flexibility that included the C␤ FG loop (28).…”
Section: Allosteric Changes In T Cell Receptor Induced By Peptide-mhcsupporting
confidence: 87%
“…Given the fluctuations in the pre-bound state, the reorganization of conformational dynamics can be probed for a variety of model interactions. Similar perturbation-based analyses have been employed in various previous studies (Ettayapuram Ramaprasad et al, 2017; Guarnera & Berezovsky, 2016; Ming & Wall, 2006; Zheng & Brooks, 2005; Zheng, Liao, Brooks, & Doniach, 2007). For further details and comparison with related approaches see Methods.…”
Section: Resultsmentioning
confidence: 97%
“…Differences in the local structural dynamics alone cannot explain the impact of FAD mutations on ε-cleavage. Although localized at a single Cα-atom or H-bond, these fluctuations may cooperate to produce functional backbone flexibility enabling (i) large-scale conformational changes conducive to recognition and binding, (ii) induced conformational relaxations, and (iii) communication between functional sites distal in the sequence (Clarkson, Gilmore, Edgell, & Lee, 2006; Csermely, Palotai, & Nussinov, 2010; Ettayapuram Ramaprasad, Uddin, Casas-Finet, & Jacobs, 2017; Guarnera & Berezovsky, 2016; Haliloglu & Bahar, 2015; Marcos, Crehuet, & Bahar, 2011; Nashine, Hammes-Schiffer, & Benkovic, 2010). The dynamic cross-correlation mainly depends on the fold and is fine-tuned by sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations